2016
DOI: 10.4314/ajtcam.v13i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Traditional, complementary and alternative medicine use in a community population in Lao PDR

Abstract: Background: The aim of this study was to assess the prevalence and associated factors of Traditional, Complementary and Alternative Medicine (TCAM) use in a community setting in a central province of Lao PDR. Materials and Methods: A cross-sectional community survey in 4 urban and 4 rural districts was conducted with the International Complementary and Alternative Medicine Questionnaire (I-CAM-Q). Results: Of the 1600 participants in the survey, the overall prevalence of any TCAM use (providers, products or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…In agreement with some previous studies [4,[25][26][27][28][29][30][31], this study found that in unadjusted analysis older age (≥60 years) was associated with AYUSH and THP utilization. Several studies showed that female sex was associated with TCM provider use [4,25,30], which in this study was found for AYUSH utilization but not for traditional health practitioner utilization.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with some previous studies [4,[25][26][27][28][29][30][31], this study found that in unadjusted analysis older age (≥60 years) was associated with AYUSH and THP utilization. Several studies showed that female sex was associated with TCM provider use [4,25,30], which in this study was found for AYUSH utilization but not for traditional health practitioner utilization.…”
Section: Discussionsupporting
confidence: 93%
“…In Vietnam, approximately 30% of all patients receive treatment with traditional medicines [ 60 ]. Especially in the health prevention and treatment of chronical disease conditions, such as stomach and intestinal disease, Gout or musculoskeletal conditions such as a chronic backache or arthritis TVM plays an important role [ 61 ]. However, the same study assessed that only 2.1% of participants used complementary and alternative medicine for the treatment of mental disorders [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the health prevention and treatment of chronical disease conditions, such as stomach and intestinal disease, Gout or musculoskeletal conditions such as a chronic backache or arthritis TVM plays an important role [ 61 ]. However, the same study assessed that only 2.1% of participants used complementary and alternative medicine for the treatment of mental disorders [ 61 ]. However, Vietnamese patients with a major depression frequently reported pain or dizziness and patients with “Phong thấp” or “neurasthenia” in the Vietnamese context frequently displayed depressive symptoms [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,19 For example, Malaysia is in the process of establishing and implementing a T&CM regulatory system that reflects the diverse forms of T&CM practiced, 20 and in Cambodia reform to strengthen regulatory systems for the health workforce has led to work underway for a legal framework for traditional medicine practitioners. 32,33 Australia and New Zealand have mixed-level recognition of T&CM. 19,29 In New Zealand, attempts are being made to integrate Māori traditional medicine (as culturally appropriate).…”
Section: Integration In Who Western Pacific Regionmentioning
confidence: 99%